Two cases of spindle cell variant diffuse large B-cell lymphoma of the uterine cervix - Hiroko Murata; Harumi Nakamura; Yukinobu Ohta; Masanori Kitamura; Shinichi Nakastuka; Jun Ishikawa; Shoji Kamiura (Elsevier, 2020)
Lymphoma with prominent spindle cell features is a morphological variant of diffuse large B-cell lymphoma (DLBCL) and is categorized as a rare variant by the WHO classification. Most cases arise from the skin, with only two cases reported in the uterine cervix to date. Here, we report two cases of spindle cell variant DLBCL of the uterine cervix. Although these cases might be rare, we believe that, as gynecologists and pathologists increase their knowledge of this variant type, more cases will be diagnosed properly.